Counterfeit Products in Online Platform: A Systematic Review - Andon , Nor Sheena (RSF Conference Series: Business, Management and Social Sciences, 2025)
The counterfeit products had been widely consumed even before the online platform usage among the consumers emerges. There are several reasons the author seeks to find on how such phenomenon occurred hence, making the purpose of this paper to identify how consumers are nowadays consuming counterfeited products impulsively through the online platform and how does it happen using the explanation of the underlying theory. The present study’s undergone a systematic review process which is the question formulation, locating studies, study selection/evaluation, analysis/synthesis and reporting/using results. The result of the study is discussed in line with the objective to answer the formulated research questions on the flow theory able to explain how online impulsive buying behaviour occurs among online users and how the online impulsive buying behaviour enhance the purchase of counterfeit products.